The effectiveness of the skill of producing mobile applications to enhancing 21st century skills - Bahkali, Hanan Mohammed; Al-Jadaani, Saja Saed; Al-Farrani, Lina Ahmad (Journal of Educational and Psychological Sciences, 2023)
This study aims at learning the role of mobile app production in developing 21st-century skills, and the study came to keep up with educational innovations and the variety of learning methods, to raise the consumer to the product class. The study used the semi-experimental applied approach to fit this research, with one experimental group. The search tool was only a questionnaire. The results found that there is a positive impact on the skills of the current century: Sensitivity to problems, collaboration, and productivity, so that the production of applications has affected them highly, the skill of collaboration has been highest with a mean value (2.90), followed by the ratio of the Sensitivity to problems skill approach with a mean value (2.85) and finally productivity skill with a mean value (2.75). Despite the different arithmetic averages, there was a clear and high effect, and the researchers recommended that the teaching courses of the skills of the current century include the introduction of mobile learning style and its applications and the care to spread useful and useful applications among students to make use of them and enable them to facilitate the learning mechanism. Pay attention to the preparation of courses for students and teachers within the boundaries of mobile learning, applications, and skills of the current century, undertake studies and research in mobile learning, application fields, and other skills of the current century, Align the skills the student learns with the skills required for the future career.